Violência por parceiro íntimo entre homens gays: caracterização, associações com estresse de minorias e avaliação da viabilidade de uma intervenção em grupo - Freitas, Renita de Cássia dos Santos (Universidade Federal de São Carlos, 2026)
This dissertation investigated intimate partner violence (IPV) in relationships among gay men in Brazil, integrating two complementary studies: a cross-sectional quantitative survey aimed at characterizing IPV and examining its associations with minority stress indicators, and a second study focused on assessing the feasibility of a remote secondary prevention intervention using a mixed methods approach. The first study included 60 adult gay men living in Brazil (Mage = 35 years), most of whom were cisgender and from the Southeast region. The Revised Conflict Tactics Scale (CTS-2) and the Minority Stress Protocol were used to assess internalized homonegativity, sexual orientation disclosure, and experiences of stigma. Descriptive and correlational analyses were conducted. A high prevalence of IPV involvement in the past year was observed, with 80% reporting victimization and 63.33% reporting perpetration. Psychological violence was the most frequent form, followed by sexual and physical violence. Strong bidirectionality was observed in relationship dynamics. Experiences of stigma showed more consistent associations with different forms of IPV, whereas internalized homonegativity and sexual orientation disclosure were not directly associated with this outcome. The second study, using a quasi-experimental mixed-methods design, involved the development, implementation, and feasibility evaluation of a remote group-based intervention. Guided by Bowen et al.'s (2009) feasibility framework, the study assessed acceptability, implementation, and practicality. The intervention consisted of synchronous online group meetings and asynchronous activities addressing IPV recognition, minority stress, emotional regulation, and assertive communication. Exploratory quantitative indicators and qualitative data (field notes and participant reports) were analyzed in an integrated manner. Findings indicated satisfactory levels of acceptability and feasibility, with recommendations for increasing the number of sessions. By integrating national prevalence estimates with the evaluation of an affirmative intervention proposal, this dissertation contributes to the advancement of preventive strategies that are sensitive to the psychosocial and contextual specificities shaping intimate relationships among gay men in Brazil.
Intimate partner violence among gay men: characteristics, associations with minority stress, and feasibility of a group-based intervention
Violencia de pareja íntima entre hombres gay: caracterización, asociaciones con el estrés de minorías y evaluación de la viabilidad de una intervención grupal
Keywords: violência por parceiro íntimo; homens gays; estudo transversal; viabilidade intervenção; LGBTQ+; intimate partner violence; minority stress; feasibility study; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL; 3. Saúde e Bem-Estar